Mercury contamination of sediments at Indonesia Ciujung watershed: contribution of artisanal small-scale gold mining - Willy C. Nugraha; Huiho Jeong; Phan Dinh Quang; Randy Novirsa; Tomohiro Komorita; Ishibashi Yasuhiro; Jun Kobayashi; Koji Arizono; Asep Bayu Dani Nandiyanto (Записки Горного института)
Artisanal small-scale gold mining is the largest artificial source of mercury pollution and has been a very common problem recently. This study examined the contribution of Hg release due to artisanal small-scale gold mining in contaminating the sediment of the watershed in Indonesia. Different from other methods, we measured Hg pollution using the stable isotopes of carbon and nitrogen. This report is the first time analytical reports in Indonesia since most papers focus primarily on only detecting heavy metals in river water and sediments, neglecting deep research on Hg pollution and resources. The findings of this study indicate that artisanal and small-scale gold mining activities, located in the upstream areas of the tributaries that act as point sources, are the primary source of mercury in the sediment of the Ciujung watershed. The isotopes δ13C and δ15N successfully trace the Hg-contaminated sediment in the Ciujung watershed derived from the Cisimeut and Ciberang Rivers based on soil organic matter. The biological effect showed the Hg concentration in most of the sampling sites exceeded the Effects-range medium and Probable effect limit values. The Risk quotient values of Hg indicated the Hg pollution had a possibility effect on the benthic organism. Several limitations have also been added in this study and needs for further investigation.